Estrutura e propriedades de materiais eletrólitos e compósitos poliméricos e sua aplicação em capacitores eletroquímicos de dupla camada - Rodrigo Lassarote Lavall (2008)
In this work, a fundamental study of different materials (blends, composites and polymeric electrolytes), all in the solid state, was accomplished. These materials were prepared with poly(ethylene oxide) and thermoplastic polyurethane (polyether based) homopolymers and polyether copolymers, using LiClO4 as ions source, nanostructured carbon black and multi-wall carbon nanotube as conductive fillers. Additionally, a direct application of those materials, in the preparation of all solid state double layer electrochemical capacitors (supercapacitors) was achieved. The thermal, morphologic and electric properties of the materials were appraised, looking for correlation between structures and properties. A reproductive and low cost methodology for fluid preparation and layers deposition was developed. Solid polymer electrolytes were prepared having values of ionic conductivity, at room temperature, among the best ones described in the literature. It was obtained good dispersions of carbon materials, both in suspension and in the solid state. Nanocomposites with conductivity of the order of 10-5 S/cm were produced with low percolation thresholds (mainly in the systems with carbon nanotubes). The preparation of polymeric nanocomposites with carbon nanotubes is a current theme in nanoscience and, the big challenge found in this area, related with the nanotubes dispersion, was won in this work. The construction of all solid state double layer electrochemical capacitors having dimensions that allow miniaturization, prepared with polymeric material, avoiding problems of leakage of electrolytes, was executed. The capacitor prepared with composite electrode with 10% of carbon black and PEO:NPPP as polymeric matrix, presents performance, accessed by the specific capacitance (F/g), superior the other solid capacitors described in the literature, and with cyclability of more than 1000 cycles.